2005
DOI: 10.1086/427990
|View full text |Cite
|
Sign up to set email alerts
|

Photon-dominated Chemistry in the Nucleus of M82: Widespread HOC + Emission in the Inner 650 Parsec Disk

Abstract: The nucleus of M82 has been mapped in several 3 and 1 mm lines of CN, HCN, C 2 H, c-C 3 H 2 , CH 3 C 2 H, HC 3 N, and HOC ϩ using the IRAM 30 m telescope. These species have been purposely selected as good tracers of photon-dominated chemistry. We have measured in the inner 650 pc galaxy disk. Furthermore, [CN]/[HCN] ∼ 5 we have detected the HOC ϩ line with an intensity similar to that of the H 13 CO ϩ line. This implies 1 r 0 1 r 0 an [HCO ϩ ]/[HOC ϩ ] ratio of ∼40. These results corroborate the existence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 25 publications
10
92
0
Order By: Relevance
“…However, these and higher [CN]/[HCN] abundance ratios have also been found in PDR/starburst scenarios (e.g. Fuente et al 2005). The fact that we find a relatively low N(CN)/N(HCN) column density ratio, with respect to what would be expected in a pure XDR scenario, could be explained by an overabundance of HCN due to the grain-surface chemistry suggested by García-Burillo et al (2008).…”
Section: Physical Environment and Abundance Ratiossupporting
confidence: 67%
“…However, these and higher [CN]/[HCN] abundance ratios have also been found in PDR/starburst scenarios (e.g. Fuente et al 2005). The fact that we find a relatively low N(CN)/N(HCN) column density ratio, with respect to what would be expected in a pure XDR scenario, could be explained by an overabundance of HCN due to the grain-surface chemistry suggested by García-Burillo et al (2008).…”
Section: Physical Environment and Abundance Ratiossupporting
confidence: 67%
“…Out of these reactions, the addition, displacement (substitution), and rearrangements are important and more common where radicals are used as either reactants or intermediates. The reaction leading to the adenine formation in the interstellar space involves several simple neutral molecules and radicals such as HCN (Jiurys 2006), HCCN (Guelin & Cemicharo 1991), NH 2 CN (Turner et al 1975), and CN (Fuente et al 2005), and belongs to the second category in which both addition and atom abstraction take place. We found that the formation of adenine in the gas phase as well as in the water containing icy grains takes place in six steps.…”
Section: Resultsmentioning
confidence: 99%
“…The rate coefficient for this reaction is estimated to be 6.24 × 10 −12 cm 3 s −1 in the gas phase ( Table 2). The next step (step 4, Table 2) in the formation of the pyrimidine ring involves the closure of the incomplete ring of molecule 3 to yield molecule 4 (2,4 dihydro-3H-purine-6-amine) through the addition of a cyanide radical which is quite abundant in the interstellar space (Fuente et al 2005). The Mulliken population analysis of molecule 3 gives net atomic charges of +0.073 and -0.465 e.s.u.…”
Section: Formation Of Six-membered Pyrimidine Ringmentioning
confidence: 99%
“…Unlike other complex molecules such as CH 3 OH, methyl acetylene shows high column densities and relative abundances in M 82 (N = 8.5 × 10 14 cm −2 , N/N H 2 = 1.1 × 10 −8 ). Since this molecule might be easily photo-dissociated by intense UV fields (Fuente et al 2005), lower abundances would have been expected in a PDR nucleus like the center of M 82. -The high J lines of HC 3 N trace the warmest gas, reaching rather high rotational temperatures of 73.3±14.0 K in NGC253 and 70.6±21.2 K in IC 342.…”
Section: Lte Analysis: Determination Of Rotational Temperaturesmentioning
confidence: 99%
“…First, its column density in M 82, of 8.5 × 10 14 cm −2 , is a factor of ∼4 larger than that of CS, and more than one order of magnitude than the HC 3 N one. Its high fractional abundance with respect to H 2 , 1.1 × 10 −8 , is puzzling for a molecule which is supposed to be easily dissociated in PDRs (Fuente et al 2005). The comparison with other molecular clouds dominated both by UV radiation and shocks, in the Galactic Center and in external galaxies, shows that M 82 is the galaxy with the highest CH 3 CCH abundance observed up to now.…”
Section: Evolved Starburst: M 82mentioning
confidence: 99%